1988
DOI: 10.1042/bj2490037
|View full text |Cite
|
Sign up to set email alerts
|

Short- and longer-term regulation of very-low-density lipoprotein secretion by insulin, dexamethasone and lipogenic substrates in cultured hepatocytes. A biphasic effect of insulin

Abstract: 1. The precise effects of insulin, dexamethasone and lipogenic precursors on the secretion of very-low-density lipoprotein (VLDL) cholesterol and triacylglycerol were dependent on the age of the culture and the duration of treatment. 2. The rates of secretion of triacylglycerol and cholesterol gradually declined with the age of the culture, although there was no detectable decrease within a given 24 h period. 3. Between 4 h and 24 h after cell preparation, insulin inhibited VLDL secretion. Inhibition was maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 39 publications
6
55
0
Order By: Relevance
“…By contrast, studies using rat livers VLDL apoB secretion in men with visceral obesity FM Riches et al have shown that in the long-term, insulin stimulates VLDL apoB secretion. 45,46 This may however, have been due to development of insulin resistance via insulin receptor downregulation. Our ®ndings suggest that in visceral obesity there is increased secretion of VLDL apoB which may in part be due to loss of sensitivity to the normal insulin-mediated suppression of VLDL apoB secretion.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, studies using rat livers VLDL apoB secretion in men with visceral obesity FM Riches et al have shown that in the long-term, insulin stimulates VLDL apoB secretion. 45,46 This may however, have been due to development of insulin resistance via insulin receptor downregulation. Our ®ndings suggest that in visceral obesity there is increased secretion of VLDL apoB which may in part be due to loss of sensitivity to the normal insulin-mediated suppression of VLDL apoB secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Culture of hepatocytes with insulin for 6-48 h results in the inhibition of secretion, whereas more prolonged culture (up to 72 h) results in stimulation of secretion (over a diminishing control value) [142][143][144]. Although this phenomenon has not always been observed [6,145], it has been interpreted as indicating that insulin acts acutely on the liver to inhibit TAG secretion, whereas, when the liver is chronically exposed to high levels of insulin, it becomes resistant to the hormone and the effect is lost.…”
Section: Experimental Observations For a Role Of Insulin In Tag Secrementioning
confidence: 99%
“…Hepatocytes were prepared under sterile conditions from rats weighing between 220 and 280 g at 10 AM (2 hours into the light phase of the cycle), as described previously. 13 The isolated hepatocytes were suspended at a concentration of 0.65ϫ10 6 cells/mL in Waymouth's medium MB752/1 containing glucose (25 mmol/L), methionine (0.33 mmol/L), fetal bovine serum (10% v/v), penicillin (90 000 U/L), streptomycin (90 000 g/L), glutamine (3.6 mmol/L), alanine (0.36 mmol/L), and serine (0.45 mmol/L). The cell suspension (3.0 mL) was plated out onto collagen-coated dishes, 39 and the cells were allowed to form a monolayer (3 to 4 hours).…”
Section: Maintenance Of Animals and Preparation Of Hepatocyte Culturesmentioning
confidence: 99%
“…This medium is subsequently referred to as supplemented medium. 13,14 At this stage, glucose was added to give initial concentrations of 0, 5, 10, 15, 20, or 25 mmol/L. Hepatocytes were cultured for 24 hours, the medium was removed, and the cells were harvested.…”
Section: Maintenance Of Animals and Preparation Of Hepatocyte Culturesmentioning
confidence: 99%
See 1 more Smart Citation